Studi Toleransi Dalam Perspektif Al-Qur’an - Purwanti, Heni; Rifa’i, Bashori; Rahmawati, Ana (Institut Darul Quran Payakumbuh, 2025)
Tolerance is a fundamental values ​​taught in the Qur'an as a foundation for creating a harmonious and civilized society. The Qur'an encourages humanity to respect differences, whether in ethnicity, nation, or belief, and to prioritize unity and justice. The purpose of this study is to examine the values ​​of tolerance and national education in several verses of the Qur'an, namely Qs. Surat Al-Kafirun,Qs. Yunus, Qs. Al-Hujurat. The research method used is the library research method. The results of the study on tolerance in Surah Al-Kafirun: Teaches religious freedom and respects differences in beliefs, with the principle